Karl Barth and the resurrection of the flesh the loss of the body in participatory eschatology - Hitchcock, Nathan (Cambridge : James Clarke & Co., 2013)
Early Christian writers preferred to speak of the coming resurrection in the most bodily way possible: the resurrection of the flesh. Twentieth-century theologian Karl Barth took the same avenue, daring to speak of humans' eternal life in rather striking corporeal terms. In this study, Nathan Hitchcock pulls together Barth's doctrine of the resurrection of the flesh, anticipating what the great thinker might have said more systematically in volume V of his 'Church Dogmatics'. Provocatively, Hitchcock goes on to argue that Barth's description of the resurrection - as eternalization, as manifest.
THE ETERNALIZATION OF THE RISEN CHRISTTHE LIMITATION OF THE HUMAN; THE ETERNALIZATION OF THE RISEN HUMAN; 4. The Resurrection of the Flesh as Manifestation; THE INTEGRITY OF THE SON; THE MANIFESTATION OF JESUS CHRIST; THE AMBIGUITY OF THE HUMAN; THE MANIFESTATION OF THE HUMAN; 5. The Resurrection of the Flesh as Incorporation; THE COMMUNION OF THE SPIRIT; THE INCORPORATION OF THE RISEN CHRIST; THE ISOLATION OF THE HUMAN; THE INCORPORATION OF THE RISEN HUMAN; 6. A Future in the Flesh; SUMMARY OF CRITIQUES; BARTH AND THE TWO TRAJECTORIES; ASCENDING TO HEAVEN OR RAISED ON EARTH?; Bibliography.
Includes bibliographical references.
Master record variable field(s) change: 072
Keywords: Barth, Karl, -- 1886-1968.; Barth, Karl, -- 1886-1968.; Resurrection -- History of doctrines; Eschatology -- History of doctrines; RELIGION -- Christian Theology -- Eschatology; Eschatology -- History of doctrines; Resurrection -- History of doctrines; RELIGION / Christian Theology / General; Electronic books